Critical Discourse Analysis of Textual Dimensions in the Editorial of Derap Guru Magazine - Hidayatul Khotimah; Sri Suciati; Ika Septiana; Nazla Maharani Umaya (Green Publisher Indonesia, 2025)
Mass media plays a crucial role in shaping public perception of the teaching profession through discourse construction and representation strategies. This study analyzes the editorial discourse in Derap Guru magazine using the critical discourse analysis approach based on Norman Fairclough's theory. Data were obtained from the print edition of Derap Guru magazine published in 2024. The problem in this study concerns how the representation of teachers in the editorial column of Derap Guru magazine is examined through a critical discourse analysis study of the textual dimension. The purpose of this research is to describe the representation of teachers in Derap Guru magazine published in 2024. The research method used is a qualitative descriptive approach, presenting data in the form of words, phrases, and sentences rather than numbers resulting from statistical calculations. The findings indicate that the representation of teachers in Derap Guru magazine is biased in favor of teachers. This is evident in the media’s tendency to emphasize certain aspects that contribute to building stigma or a particular perception of teachers as a group. The tendency to highlight specific issues constructs stigmas or perceptions about teachers as a professional body, revealing tensions between state policies, digital literacy demands, compensation adequacy, and professional respect. This research contributes to understanding how specialized educational media employs discourse strategies to advocate for teacher interests while upholding journalistic credibility.